MARY AS A SELFISH MOTHER IN JANE AUSTEN’S PERSUASION: A PSYCHOANALYTICAL CRITICISM - Fakhrani Zullefi; Rika Handayani (Krinok:Jurnal Linguistik Budaya, 2026)
This article examines the portrayal of motherhood in Jane Austen’s Persuasion (1817), focusing on the supporting character Mary Musgrove, who is depicted as a selfish and emotionally detached mother. The study aims to identify the factors that shape Mary’s selfishness and to explain how her childhood experiences influence her behavior as an adult and as a mother. This research applies Sigmund Freud’s theory of the dynamics of personality (id, ego, and superego) and Nancy Chodorow’s concept of the reproduction of mothering, as outlined in The Reproduction of Mothering: Psychoanalysis and the Sociology of Gender (1978). A qualitative method was used, with Persuasion as the primary data source and relevant journal articles and books as secondary data; the analysis was carried out through close reading, thematic analysis, and interpretation, then presented descriptively. The findings show that Mary’s selfishness stems from an imbalance between her id, ego, and superego, in which her id-driven need for attention dominates while her superego fails to instill a sense of maternal obligation. Five interrelated factors are identified as contributing to her selfish mothering: the effects of early mothering, the mothering relation and self-identity, maternal ambivalence and emotional influence, social and psychological expectations of mothering, and unresolved preoedipal conflicts. These factors, rooted in Mary’s own emotionally unavailable upbringing, in turn affect her sons’ emotional security, trust, and long-term capacity for healthy attachment